Chameleon effect and colour stability of nano-filled resin composites: an in-vitro study - Chiong, Amanda Swee Yee; Ethan, Ting Sheng; Sofya Zulkiffli; Noor Azlin Yahya (Penerbit Universiti Kebangsaan Malaysia, 2025)
This laboratory experimental study evaluated the chameleon effect and colour stability of three resin composites: SOLARE Sculpt (SL), Essentia (ES), and SimpliShade (SS), after immersion in distilled water, coffee, coke, and turmeric. Twenty class III restorations (shade A2) were placed on central incisors using the three materials and assessed for the chameleon effect with a digital colourimeter. To test colour stability, 120 circular specimens (10 mm diameter, 2 mm thickness) of each material (n=40) were immersed in distilled water, coke, coffee, and turmeric for 1, 7, and 30 days. Colour changes were measured using spectrophotometry. Results showed no significant differences in the chameleon effect among the materials (p > 0.05). However, colour stability varied significantly over time and across staining solutions. Turmeric caused the greatest discolouration, followed by coffee, Coke, and distilled water, with ES generally more susceptible to staining and SS showing the highest colour change in turmeric. These findings suggested that while the chameleon effect was similar across all materials, colour stability varied, with coffee and turmeric contributing more to staining. Clinicians can use this information to select materials based on patients’ dietary habits and emphasize the importance of routine restorative maintenance for long-term aesthetic outcomes.